The Influence of Myocardial Revascularization on the Condition of the Distal Part of Coronary Arteries in Patients with Type 2 Diabetes Mellitus - Georgiy B. Mankovsky; Yana Yu. Dzhun (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the dynamics of the internal lumen of the distal part of coronary arteries after percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) in patients with type 2 diabetes mellitusMaterials and methods. This retrospective study included 121 patients with coronary artery disease and type 2 diabetes mellitus after revascularization of coronary arteries through PCI or CABG. In order to evaluate the changes in the condition of the distal sections of the coronary arteries after stenting and CABG, we included patients with type 2 diabetes mellitus in whom repeated coronary angiography was performed 12-60 months after PCI or CABG. The quantitative method (quantitative coronary angiography) and semi-quantitative assessment scales were used to assess the dynamics of the distal part of the coronary arteries.Results. The mean age of the patients was 56.2 ± 0.4 years for patients who underwent CABG and 54.3 ± 0.4 years for patients who underwent PCI. There were 64.7% men in the CABG group and 54.0% in the PCI group. The use of drug-eluting stents didn’t affect the internal lumen of the distal part of the arteries. After implantation of bare metal stents, progression of diffuse atherosclerotic lesions was detected. The use of arterial grafts during CABG improved the condition of the inner lumen of the bypassed vessel. However, after venous grafts placement, the patency of the distal coronary arteries may deteriorate in the future.Conclusions. In people with type 2 diabetes mellitus and coronary artery disease, after cardiac surgery, the smaller branches of the blood vessels can become narrower over the next 1-5 years if a stent without medication or a vein graft is used. However, when a drug-eluting stent or an artery graft is used, the smaller vessel branches stay about the same or even improve over time.